Tributaries - Da̕, Laura (Book collections on Project MUSE., 2015)
"This poetry manuscript combines lyrical, historical, personal, and narrative poetry. The narrative scope of the manuscript moves from the period of Indian Removal in the 1830s through the period of Allotment and the Dawes Act of the 1900s and into the present"--Provided by publisher